2022
DOI: 10.1038/s41598-022-17943-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between dose of hemodialysis and patients mortality in a prospective cohort study

Abstract: Dialysis adequacy is a known risk factor for mortality in maintenance hemodialysis (MHD) patients. However, the optimal dialysis dose remains controversial. Therefore, we aimed to explore the relationship between dialysis dose and all-cause and cardiovascular disease (CVD) mortality among MHD. We examined the associations of dialysis dose with mortality in a cohort (n = 558) of MHD patients from 31 December 2015 to 31 December 2020. Dialysis adequacy was assessed using baseline Single-pool Kt/Vurea (spKt/V), w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…Besides, worldwide, kidney replacement therapy is more commonly provided to men than women, possibly due to biological factors and the accelerated development of chronic kidney disease in men. The current result was similar to Liu et al, [35] and Lima et al, [36] who noticed that 50% of respondents were males. Pertaining to residence, the current research results proved that approximately three quarters of the participants originated from rural regions.…”
Section: Discussionsupporting
confidence: 91%
“…Besides, worldwide, kidney replacement therapy is more commonly provided to men than women, possibly due to biological factors and the accelerated development of chronic kidney disease in men. The current result was similar to Liu et al, [35] and Lima et al, [36] who noticed that 50% of respondents were males. Pertaining to residence, the current research results proved that approximately three quarters of the participants originated from rural regions.…”
Section: Discussionsupporting
confidence: 91%
“…Second, as a result of long-term hemodialysis, MHD patients’ physical function, muscle strength, and functional motor ability have declined, their social function has gradually weakened, and they have become more dependent on their caregivers for support and assistance, which has brought double pressure on the patients’ body and psychology, and exacerbated social alienation. Lastly, MHD patients have high rates of cardiovascular events and mortality [ 15 , 71 ], and patients have negative perceptions of the disease [ 72 ], leading to fear of disease progression and increased social alienation.…”
Section: Discussionmentioning
confidence: 99%
“…The NKF-KDOQI guidelines recommend that for patients with low residual natural renal clearance (KRU, 2 mL/min), the target dialysis dose for thrice-weekly HD is 1.2–1.4 spKt/V per dialysis [ 6 ]. It has been shown that spKt/V is a significant predictor of morbidity and mortality in patients receiving HD [ 20 , 21 ]. Studies have shown a strong correlation between Kt/V and mortality in HD patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%